Formation of accounting and analytical support of the enterprise cost management system (Economics and region, 2022)
Effective functioning of the enterprise cost management system is possible only if there is complete, reliable and objective information. The main source of information formation in the enterprise management system is accounting. It is substantiated that the primary task in creating a rational enterprise management system is the formation of high-quality accounting information that would satisfy the needs of all users who need such information to make informed and rational decisions in the shortest possible time. It is suggested that traditional accounting, which is the basis of information support for making effective strategic and tactical management decisions, does not fully meet the requirements of users, so there is a need to consolidate information from non-financial sources to make effective management decisions. The necessity of forming a new accounting and information system, which should contain organized organizational information about the state of management objects, adapted to modern management tasks, is argued. The article considers the process of formation of accounting and analytical support of the enterprise cost management system, which consists in consolidation of accounting and non-accounting information (at the intersection of such subject areas as accounting, management, corporate information systems). The issues of structuring the internal environment of the enterprise and the allocation of responsibility centers (control center, costs, income, etc.) for setting goals for management subsystems are investigated. It is proved that by comparing the actual costs with the planned (normative) it is possible to evaluate the work of all departments in terms of resource use, to identify the causes of deviations of actual costs from the planned. The analysis of scientific works of domestic scientists and generalized the definition of "cost management system", as well as formed the principles and requirements for the consolidation of accounting and analytical information on cost management.
Keywords: accounting system; accounting and analytical support; cost management; accounting information; consolidated information